Study on satellite broadcasting scheduling based on Particle Swarm Optimization algorithm - Kewen Xia; Fei Zheng; Yue Chi; Rui Wu (2009 IEEE International Conference on Communication Technology and Applications, 2009)
The efficiency of utilizing the satellite communications resource and system can be improved by optimizing the satellite broadcasting scheduling with genetic algorithm. However drawbacks such as complicated genetic operation, tardy convergent speed and the aptness to sink into local minimum within the genetic algorithm (GA) have encouraged a satellite broadcasting scheduling approach for resolving the scheduling model. The approach was based on the particle swarm optimization (PSO) algorithm which involved in processes such as constructing the model of satellite broadcasting scheduling, initialization of the particles and particle optimization. It has been shown by simulation analysis that satellite broadcasting scheduling based on the PSO algorithm was feasible and its optimization result was significant.